2011
DOI: 10.1155/2011/537634
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of a Creative Bonding Intervention to Promote Nursing Students' Attitudes towards Taking Care of Older People

Abstract: Although numbers of older people are increasing, nursing students have negative attitudes towards older people and do not plan to care for them following graduation. Multiple strategies have been implemented to reverse students' attitudes with mixed results. The purpose of this pilot quasi-experimental study was to test a Creative-Bonding Intervention (CBI) with students implementing art activities with older people to promote students' willingness to take care of them. Using a self-transcendence conceptual fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…However, the study was inconsistent with the study of Chen and Walsh (2009) showed that the nursing intervention didn't improve self-transcendence level of the students significantly (Chen and Walsh, 2009). Also in Lamet et al study which assessed the intervention effect for developing perspective of nursing students in elderly care, there was no significant different before and after the intervention in self-transcendence (Lamet et al, 2011) and this differences can be related to the target group of Reed's theory that was the nursing students. Nursing students experience situations of taking care of the elderly during their education repeatedly that can be the reason of the lack of student's selftranscendence increasing level, but in this study and Jadid-Milani's et al study, there were patients who had more vulnerability because of their chronic diseases and they felt more self-transcendence to reach higher life quality (Jadid-Milani et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the study was inconsistent with the study of Chen and Walsh (2009) showed that the nursing intervention didn't improve self-transcendence level of the students significantly (Chen and Walsh, 2009). Also in Lamet et al study which assessed the intervention effect for developing perspective of nursing students in elderly care, there was no significant different before and after the intervention in self-transcendence (Lamet et al, 2011) and this differences can be related to the target group of Reed's theory that was the nursing students. Nursing students experience situations of taking care of the elderly during their education repeatedly that can be the reason of the lack of student's selftranscendence increasing level, but in this study and Jadid-Milani's et al study, there were patients who had more vulnerability because of their chronic diseases and they felt more self-transcendence to reach higher life quality (Jadid-Milani et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…However, the study on improving the self-transcendence level and positive attitude to take care of the elderly in nursing students showed that the self-transcendence level had no meaningful changes before and after intervention (Chen and Walsh, 2009;Lamet et al, 2011). The studies showed that self-transcendence has a significant effect on increasing self-care in patients (Mellors et al, 1997;Upchurch and Mueller, 2005), having goals in life (Nygren et al, 2005), and life quality in patients with incurable diseases (Jadid-Milani, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Creative Bonding Intervention (CBI) showed significant positive change in student nurse attitudes toward older adults and willingness to care for them after students implemented art activities with the elderly [24]. Walton and Blossom [25] noted similar positive experiences with student nurses and older adults who partnered in a home visiting program called Healthy Partners (HP).…”
Section: Fostering Positive Attitude Creative Learning Activitiesmentioning
confidence: 99%
“…Within the literature review, several studies used the same instruments, while some created tools were specific to individual studies. The similar instruments included Kogan's Attitudes Toward Old People Scale (KATOP), Attitudes Toward Old People (ATOP) questionnaire, and Aging Semantic Differential (ASD) [8,11,13,14,23,24] Neville [26] identified inconsistencies with psychometric characteristics of the eight instruments analyzed. Related concepts are sometimes used interchangeably and incorrectly such as the ASD scale, which interchanges the terms "attitude" with "stereotype".…”
Section: Measuring Attitudes Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation